Therapeutic potential of fruit mulberry: a systematic review of pharmacological activities and mechanistic insights - P. Lokeshkumar; R. Shanmugam; K. A. Murugesh; B. Vinothkumar; P. Jaisridhar (Phytochemistry Reviews, 2026)

Exploitation of Chaetomium globosum and AMF against Macrophomina phaseolina causing root and crown rot in strawberry and its underlying mechanisms by molecular docking - I.S. Jothini Varsha; L. Rajendran; K. Saravanakumari; G. Karthikeyan; B. Vinothkumar; R. Anandham (Physiological and Molecular Plant Pathology, 2025)

Symbiosis in Sea Anemones: A Few Case Reports Along the Bay of Bengal Large Marine Ecosystem - L. Ranjith; R. Saravanan; S. Ramkumar; C. Kalidas; R. Vinothkumar; D. Linga Prabu; M. Kavitha; A. Mathan Babu; R. Kalaibharathi; P. S. Asha (Marine Ecology, 2025)
The most well‐known relationship is between sea anemones and decapod crustaceans, of which crabs are classic examples of mutualistic interactions in which both organisms benefit from living with zooxanthellae and hermatypic or reef‐forming corals. A marine ecology study off the southern coast of Tamil Nadu revealed five types of sea anemones that cohabit symbiotically with other marine animals. These species include Stichodactyla haddoni (Saville‐Kent, 1893), Entacmaea quadricolor (Leuckart in Ruppell and Leukart, 1828), Radianthus (= Heteractis ) magnifica (Quoy and Gaimard, 1833), Radianthus (= Heteractis ) crispa (Ehrenberg, 1834), and Calliactis polypus (Forsskal, 1775), are found in symbiotic associations. This observation revealed that the decapod porcelain crab Neopetrolisthes is associated with the sea anemones Radianthus and Entacmaea , whereas this has not been reported in Stichodactyla . The hermit crab anemone, C. polypus , is generally associated with hermit crabs, and we report this association for the first time in live gastropod, Turbinella pyrum (Linnaeus, 1767). A few animals (both the host and symbiont) were brought to the cnidarian laboratory at the ICAR‐Tuticorin Regional Station of the CMFRI, where they were maintained in optimum seawater for further observations. The present study aimed to compare previous reports of symbiosis in decapod crustaceans and gastropods with sea anemones from Indian waters to provide insight into the dynamics of symbiosis in the Bay of Bengal Large Marine Ecosystem.

Manifestation of UiO-66-Zr MOF-enabled photocatalytic membranes for successive separation and degradation of dye mixtures in water remediation - K. Gayathri; K. Vinothkumar; Sakar Mohan; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2024)

Untangling the taxonomic ambiguities of the spotted seerfish Scomberomorus guttatus with the description of a new species from India - Eruppakkottil M. Abdussamad; Thomas Toji; Amalraj M. R. Margaret; Kalappurakkal G. Mini; Kothanahally M. Rajesh; Pokkathappada A. Azeez; Vinothkumar Ramar; Thayichira B. Retheesh; Athikkattil M. Abbas; Ismail Shihab; Sneha M. George; Rohith Prathibha; et al. (Journal of Fish Biology, 2024)
Scomberomorus guttatus has been subjected to a series of synonym assignations over the years. Its taxonomy has been mired with ambiguities due to the greater‐than‐average morphological variations observed in samples from different regions. An integrated taxonomic revision with molecular support indicated that the species that was thought to be a single entity, in reality, is a complex of three distinct species. They are morphologically distinct with respect to the body depth and elongation, cephalic morphometry, and meristic characteristics. Otolith morphometry and phylogenetic evidence further established the taxonomic divergence within the spotted seerfish complex. The phylogenetic characteristic as indicated by the mitochondrial Cytochrome c Oxidase subunit I (COI) sequence unveiled that S. guttatus had a high intraspecific divergence of 11.1% from its two identical congeners and a divergence of 2.34% between the congeners, indicating scope for categorizing them as separate species. Based on the morphological and molecular evidence, S. guttatus is redescribed; the senior synonym Scomberomorus leopardus is resurrected as a valid species; and a new species Scomberomorus avirostrus n. sp. is described with keys for species distinction.

MIL-100 (Fe) integrated fibrous polyvinyl alcohol graft on cellulose acetate towards the development of green membranes; Application in multi solute rejection - Lavanya Chandra; Karthikeyarajan Vinothkumar; R Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2023)

Resolved and Redeemed: A New Fleck to the Evolutionary Divergence in the Genus Scomberomorus Lacepède, 1801 (Scombridae) With Cryptic Speciation - N. S. Jeena; Summaya Rahuman; Subal Kumar Roul; P. Abdul Azeez; R. Vinothkumar; H. M. Manas; E. A. Nesnas; A. Margaret Muthu Rathinam; S. Surya; Prathibha Rohit; E. M. Abdussamad; A. Gopalakrishnan (Frontiers in Marine Science, 2022)
The genus Scomberomorus , with 18 nominal species, sustains a significant heterogeneous fishery throughout its range. The sole molecular systematic study of this genus concerned the species group S. regalis , which contains the new world taxa. The species diversity of Scomberomorus in the northern Indian Ocean has not been studied at the molecular level, often leading to misidentifications. Here, novel genetic data are provided that reconfigure species boundaries from the region. We used single and multilocus data (eight mitochondrial and three nuclear genes) to infer phylogenetic relationships, species delimitation, and the resurrection of a time-calibrated phylogenetic tree. Our aim was also to verify the hypothesis of geographical races in S. guttatus predicated on variable vertebral counts. Interestingly, all species delimitation analyses have recovered another highly cryptic species in the nominal S. guttatus previously believed to have an Indo-Pacific distribution . Scomberomorus guttatus (Bloch and Schneider, 1801) in the sensu stricto , is redeemed from its type locality based on genetic data and preliminary morphomeristic investigations and has a restricted distribution in the Bay of Bengal. The cryptic species Scomberomorus aff. guttatus which exhibits >10% genetic divergence from S. guttatus is resurrected here from the synonymy of the latter as Scomberomorus leopardus (Shaw, 1803). Widespread in the Indo-Pacific, this species contains two major molecular operational taxonomic units (MOTUs) with a divergence threshold of over 2% between them. Our analysis suggests that vertebral counts must be coupled with other features to identify the species/lineages in the nominal S. guttatus. The heterogeneity in the S. guttatus species group is discussed in relation to the ecological diversity of the region which facilitates larval recruitment and niche specialization. The results also revealed two allopatric putative species in S. commerson , found primarily in the Pacific and Indian Oceans. This study added genetic data from S. lineolatus and S. koreanus , not previously represented in the sequence repositories. Estimation of divergence time indicated that the Indo-West Pacific species group undergoes multiple diversification events besides the recent splits detected within S . leopardus .

Postulating the Modality of Integrative Taxonomy in Describing the Cryptic Congener Pampus griseus (Cuvier) and Systematics of the Genus Pampus (Perciformes: Stromateidae) - Subal Kumar Roul; N. S. Jeena; Rajan Kumar; R. Vinothkumar; Shikha Rahangdale; Summaya Rahuman; Shubhadeep Ghosh; Prathibha Rohit; Achamveetil Gopalakrishnan (Frontiers in Marine Science, 2021)
Pomfrets (genus Pampus ), a highly commercial fishery resource distributed in the Indo-Western Pacific that includes Lessepsian migrants, have witnessed a series of systematic reforms. In this study, based on comprehensive sampling spanning type localities and coevals in the Northern Indian Ocean, the cryptic and valid species Stromateus griseus is resurrected from the synonymy and re-described as Pampus griseus (New Combination) based on 35 specimens from the Bay of Bengal, corroborated by a molecular analysis, which indicated a confined distribution of the species. The Bayesian phylogeny of the genus was reconstructed, incorporating redressed barcodes (582 nucleotides) and concatenated mitochondrial gene sequence data (1,822 nucleotides) generated from the recorded species P . candidus , P . chinensis and the neophyte along with sequences from GenBank entrusting the latest literature. The phylograms differed in topology as for seven valid species, and the one predicated on the concatenated data erected a highly supported polytomous clade for the P . cinereus complex ( P . griseus , P . cinereus , and P . candidus ) which shares synapomorphies. Pampus argenteus and P . minor , together, formed a sister clade to the rest. Climate-driven vicariant events during glacial epochs and the Indo-Pacific Barrier effect can be the drivers behind the Indian and Pacific Ocean sister lineages in P . chinensis . A multivariate analysis isolated the cryptic species from its congeners. This article portrays the systematics revision of genus Pampus with an integrative taxonomic approach compiling distinctive molecular, morphological, and anatomical features, revised key for species identification, taxonomic archives of Indian stromateids, and winds up with specific remarks.

Isolation and characterization of heterotrophic nitrification–aerobic denitrification and sulphur-oxidizing bacterium Paracoccus saliphilus strain SPUM from coastal shrimp ponds - Y. D. Jaffer; H. Sanath Kumar; R. Vinothkumar; A. B. Irfan; N. M. Ishfaq; Parvaiz Ahmad Ganie; Raja Adil Hussain Bhat; A. Vennila (Aquaculture International, 2019)

The resolution revolution reaches India - Ramaswamy Subramanian; Satyajit Mayor; Kutti R. Vinothkumar (Biophysical Reviews, 2019)